Fluorescence quenching and time-resolved fluorescence studies of alpha-Mannosidase from Aspergillus fischeri (NCIM 508) - Shashidhara, K. S.; Gaikwad, Sushama M. (Journal of Fluorescence, 2007)
Apart from the vital role in glycoprotein biosynthesis and degradation, alpha-mannosidase is currently an important therapeutic target for the development of anticancer agents. Fluorescence quenching and time-resolved fluorescence of alpha-mannosidase, a multitryptophan protein from Aspergillus fischeri were carried out to investigate the tryptophan environment. The tryptophans were found to be differentially exposed to the solvent and were not fully accessible to the neutral quencher indicating heterogeneity in the environment. Quenching of the fluorescence by acrylamide was collisional. Surface tryptophans were found to have predominantly positively charged amino acids around them and differentially accessible to the ionic quenchers. Denaturation led to more exposure of tryptophans to the solvent and consequently in the significant increase in quenching with all the quenchers. The native enzyme showed two different lifetimes, tau (1) (1.51 ns) and tau (2) (5.99 ns). The average lifetime of the native protein (tau) (3.187 ns) was not affected much after denaturation (tau) (3.219 ns), while average lifetime of the quenched protein samples was drastically reduced (1.995 ns for acrylamide and 1.537 ns for iodide). This is an attempt towards the conformational studies of alpha-mannosidase.
Keywords: alpha-Mannosidase; Denaturation; fluorescence; lifetime; Solute quenching